Psychological Indicators of Parental Burnout in Families with Three or More Children - Saadati, Nadereh; Atashpour, Seyed Salar; Samiei, Laya (Mental Health and Lifestyle Journal, 2024)
This study aimed to explore the psychological indicators of parental burnout among families with three or more children through a qualitative lens. Using a qualitative content analysis approach, the study recruited 23 parents (15 mothers and 8 fathers) from Isfahan, Iran, all of whom had at least three children. Participants were selected through purposive sampling to ensure variation in age, socioeconomic status, and employment. Data were collected via semi-structured interviews lasting 45–75 minutes, and interviews continued until theoretical saturation was reached. All interviews were transcribed verbatim and analyzed using NVivo software. Thematic analysis was conducted to identify major categories and subcategories of psychological distress related to parental burnout. Three overarching themes emerged: emotional exhaustion, cognitive dysfunction, and detachment with identity strain. Emotional exhaustion included persistent fatigue, emotional numbness, and an inability to recover despite rest. Cognitive dysfunction was marked by decision-making fatigue, concentration issues, and internalized self-criticism. Detachment and identity strain manifested as emotional distancing from children, role imbalance, and the erosion of personal identity. Mothers reported greater levels of guilt and emotional overload compared to fathers. Participants attributed these psychological symptoms to the cumulative demands of raising multiple children in the absence of adequate social and institutional support. The findings highlight that parental burnout in large families is a multidimensional experience affecting emotional, cognitive, and relational well-being. Cultural expectations, lack of systemic support, and internalized ideals of “good parenting” intensify this condition. Interventions should prioritize mental health resources for multi-child families and promote societal recognition of parental burnout as a legitimate psychological concern.